2014
DOI: 10.2527/jas.2013-6755
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of N-acetyl cysteine on gut redox status and major microbiota in weaned piglets1

Abstract: This study was conducted to explore the regulation of N-acetyl cysteine (NAC) on gut redox status and proliferation of selected microbiota in weaned piglets. A total of 150 newborn piglets from 15 litters were randomly divided by litter to the control group (normally suckling), the weaning group (fed the basal diet), and the NAC group (basal + NAC diet) with 5 litters per group. Activities of total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and inhibition capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…These reports are consistent with the findings of the present study that NAC increases the Akkermansia , Bifidobacterium , Lactobacillus , and Allobaculum populations, but suppresses the growth of Desulfovibrio and Blautia . This is further supported by a study in which NAC upregulated the amount of Lactobacillus and Bifidobacterium and decreased the abundance of Escherichia coli in weaned piglets . Of note, in the present study the above genera were determined to be closely associated with hyperglycemia, high endotoxin, and intestinal integrity using correlation analyses (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These reports are consistent with the findings of the present study that NAC increases the Akkermansia , Bifidobacterium , Lactobacillus , and Allobaculum populations, but suppresses the growth of Desulfovibrio and Blautia . This is further supported by a study in which NAC upregulated the amount of Lactobacillus and Bifidobacterium and decreased the abundance of Escherichia coli in weaned piglets . Of note, in the present study the above genera were determined to be closely associated with hyperglycemia, high endotoxin, and intestinal integrity using correlation analyses (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, NAC exhibits a broad antibiofilm effect towards Streptococcus pneumoniae and Haemophilus influenzae , indicating a curative effect on gut dysbiosis. So far, there have been limited studies on the effects of NAC on the community structure and function of gut microbiota . In consideration of the favorable therapeutic effect of NAC on diabetes mellitus, it is of importance to determine the role of gut microbiota in the prevention of diabetes and obesity by NAC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that Lactobacillus was negatively correlated with oxidative stress, while, conversely, E. coli showed a strong positive correlation with oxidative stress in the intestines of early weaned piglets (Xu et al, 2014a). In most cases, oxidative stress is characterized by increased generation of ROS which overwhelm the antioxidant capacity, subsequently resulting in damage to cellular macromolecules such as lipids, proteins and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of ROS in the mucosa of the jejunum are induced by changes in diet [2], and alter microbiota compositions [3,4]. Oxidation–reduction imbalance in the intestinal epithelium has an impact on its functionality [5].…”
Section: Introductionmentioning
confidence: 99%